Assessment of fat taste in individuals with and without anorexia nervosa. Issue 2 (26th November 2013) - Schebendach, Janet E.; Klein, Diane A.; Mayer, Laurel E.S.; Devlin, Michael J.; Attia, Evelyn; Walsh, B. Timothy
ABSTRACT Objective Avoidance of dietary fat is a highly characteristic eating behavior of individuals with anorexia nervosa (AN). To date, no study has determined whether these individuals are better able to perceive the fat content of foods than individuals without AN. The goal of this study was to compare blinded taste ratings of fat‐free, low fat, and regular cream cheese in patients with AN and in normal controls (NC). Method AN (n = 25) and control (NC; n = 25) participants were presented with a series of nine cream cheese samples of three differing fat contents and asked to taste and rate each sample from very low to very high fat. Results Repeated measures ANOVA found no significant main effect of fat content and no interaction between fat content and diagnosis; however, a significant three‐way interaction between fat content, diagnosis, and trial was observed. Post hoc analysis revealed a significant fat content by trial interaction within the AN group, suggesting a significant trial effect for the fat‐free samples only with improving ability to detect fat‐free samples over repeated trials. Discussion The current study suggests that individuals with AN do not have a markedly greater ability to taste fat than NC, and that; therefore, fat avoidance is likely primarily based on cognitive factors. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:215–218)